Time-series transcriptome analysis identified differentially expressed genes in broiler chicken infected with mixed Eimeria species - Kim, Minjun; Chung, Yoonji; Manjula, Prabuddha; Seo, Dongwon; Cho, Sunghyun; Cho, Eunjin; Ediriweera, Thisarani Kalhari; Yu, Myunghwan; Nam, Sunju; Lee, Jun Heon (Frontiers in Genetics, 2022)
Coccidiosis caused by the Eimeria species is a highly problematic disease in the chicken industry. Here, we used RNA sequencing to observe the time-dependent host responses of Eimeria-infected chickens to examine the genes and biological functions associated with immunity to the parasite. Transcriptome analysis was performed at three time points: 4, 7, and 21 days post-infection (dpi). Based on the changes in gene expression patterns, we defined three groups of genes that showed differential expression. This enabled us to capture evidence of endoplasmic reticulum stress at the initial stage of Eimeria infection. Furthermore, we found that innate immune responses against the parasite were activated at the first exposure; they then showed gradual normalization. Although the cytokine-cytokine receptor interaction pathway was significantly operative at 4 dpi, its downregulation led to an anti-inflammatory effect. Additionally, the construction of gene co-expression networks enabled identification of immunoregulation hub genes and critical pattern recognition receptors after Eimeria infection. Our results provide a detailed understanding of the host-pathogen interaction between chicken and Eimeria. The clusters of genes defined in this study can be utilized to improve chickens for coccidiosis control